Participation of Students with Disabilities in Physical Activities: An Attitudes of University Students - Sarma, Kamala (Nepalese Journal of Management and Technology, 2024)
Attitudes play a contributing role in inclusion. Negative attitude is a leading cause of exclusion of students with disability to participate them in physical activity. Objectives of this study were to assess the level of attitudes of college students towards participation of students with disabilities in physical activities and to analyze attitudes of sample students by gender, religion, caste, marital status, and previous contact with people with disabilities. The study was descriptive in nature. The study comprises a sample of 387 students from Tribhuvan University (TU), using convenience sampling technique. Data were collected by survey method including questionnaire including demographic variables and the scale to measure attitude. The study found that 99% respondents expressed negative attitudes towards participation of students with disabilities. The findings of study point to the need to modifying students’ attitude or the need to create awareness program to facilitate social acceptance of individual differences in the society.